Preventing Phubbing through Hadith-Based La Yahjura: An Islamic Strategy for Family Harmony in the Digital Age: (Mencegah Phubbing melalui La Yahjura Berbasis Hadis: Strategi Islam untuk Harmoni Keluarga di Era Digital) - Nadia Azkiya; Muhajirin Muhajirin; Putri Ayu (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2025)
The rapid evolution of digital technology has introduced profound challenges to interpersonal dynamics, particularly within family units, where phubbing—snubbing others in favor of smartphone engagement—erodes communication, fosters emotional distance, and undermines relational bonds. This article examines phubbing as a contemporary manifestation of social avoidance, drawing parallels to the Islamic prohibition of lā yahjura (no boycotting or ignoring beyond three days), as outlined in authentic hadiths from Sahih al-Bukhari and Sahih Muslim. The Prophet Muhammad (peace be upon him) emphasized preserving social ties to foster community harmony, a principle directly applicable to mitigating digital distractions. To operationalize this, we introduce the CARE strategy: Conscious Awareness of technology's relational costs, Active Engagement in face-to-face interactions, Responsible Usage to balance digital and real-world priorities, and Empathy Building to nurture mutual understanding. By integrating these religious imperatives with evidence-based practices, families can restore authentic connections and cultivate resilient harmony in the digital age. This interdisciplinary approach not only contextualizes Islamic ethics for contemporary issues but also offers practical, scalable interventions for global audiences.